2008
DOI: 10.2337/dc08-0331
|View full text |Cite
|
Sign up to set email alerts
|

Influence of and Optimal Insulin Therapy for a Low–Glycemic Index Meal in Children With Type 1 Diabetes Receiving Intensive Insulin Therapy

Abstract: OBJECTIVE -The purpose of this study was to quantify the effects of glycemic index on postprandial glucose excursion (PPGE) in children with type 1 diabetes receiving multiple daily injections and to determine optimal insulin therapy for a low-glycemic index meal.RESEARCH DESIGN AND METHODS -Twenty subjects consumed test breakfasts with equal macronutrient contents on 4 consecutive days; high-and low-glycemic index meals (glycemic index 84 vs. 48) were consumed with preprandial ultra-short-acting insulin, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
1
9

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 25 publications
(19 reference statements)
2
52
1
9
Order By: Relevance
“…[14] This study is limited in that only 5 subjects were involved. Further studies are required to determine the optimal ratios of insulin, insulin delivery options and non-insulin-related strategies for managing PPBG.…”
Section: Discussionmentioning
confidence: 99%
“…[14] This study is limited in that only 5 subjects were involved. Further studies are required to determine the optimal ratios of insulin, insulin delivery options and non-insulin-related strategies for managing PPBG.…”
Section: Discussionmentioning
confidence: 99%
“…GI c Seven studies (total 98 subjects) (4,6,(8)(9)(10)12,14). c All studies reported significant differences in glycemia with differing GI (same carbohydrate).…”
Section: Glycemic Indexmentioning
confidence: 99%
“…16,[29][30][31][32] Yoğun insülin tedavisi alan Tip 1 diyabetlilerde, Gİ'nin postprandiyal glisemi üzerine etkisinin incelendiği çalışmalarda, yüksek Gİ'li besinler veya öğünlerle düşük Gİ'li besinler veya öğünler karşılaştırılmış, diyet ile Gİ'nin düşürül-mesinin daha iyi glisemik kontrol sağladığı bildirilmiştir. 2,16,[29][30][31][32]35 Mohammed ve ark., eğri altındaki artış alanı-nın Gİ ile yakından ilişkili olduğunu saptamışlar-dır. Yüksek Gİ'li öğün, düşük Gİ'li öğünle karşılaştırıldığında 30. ve 180. dk arasındaki bütün zaman noktalarında daha yüksek postprandiyal glukoz seyrine neden olmuştur.…”
Section: Gli̇semi̇k İndeksi̇n Postprandi̇yal Gli̇semi̇ üZeri̇ne Etki̇si̇unclassified
“…7 Optimal prandiyal bolus zamanını araştıran çalışmalarda, insülin dozunun öğüne başlamadan önce uygulanmasının geciktirilmesiyle karşılaştı-rıldığında daha iyi bir glisemik kontrol sağladığı belirtilmektedir. [35][36][37] Smart ve ark., yağ içeriği yük-sek öğün tüketimi sonrası ani postprandiyal glukoz yükselişi zayıf olsa da öğünün karbonhidrat içeriği için hâlâ insülin ihtiyacı bulunduğunu bildirmiş-lerdir. Bu nedenle, yüksek yağlı öğünlerde insülin enjeksiyonunun geciktirilmesinin istenmeyen postprandiyal hiperglisemiye yol açabileceği ifade edilmektedir.…”
Section: Di̇yet Yağ Ve Protei̇nleri̇ İçi̇n İnsüli̇n Bolus Dozu Bolus Zamaunclassified
See 1 more Smart Citation